The Unresolved Spaces of Diasporic Desire: An Interdisciplinary Critique of Haruko Okano’s Work - Darias-Beautell, Eva (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2014)
This article explores, through the analysis of recent Asian Canadian critical and creative work, the unresolved nature of diasporic modes of cultural production in contemporary Canada. It starts by offering a metacritical discussion of Asian Canadian literary scholarship, with a focus on those works that define the field in terms of the quandary between resistance to various modes of cooption and the residual desire to belong. The second part of the article proposes an interdisciplinary critique of the poet and multimedia artist Haruko Okano’s work as providing an instance of these contradictions, as well as exemplifying the potential of creative practices to provide answers to critical and theoretical impasses. Okano’s disconcerting writing and artwork have invariably revolved around the unresolved condition of cultural hybridity, often betraying the traps as well as the possibilities of the search for modes of expression that fall outside normativity. Her production may thus be read metacritically, in that it thematizes and speaks to the theoretical debates that surround the condition of the diasporic subject in Canada.